An Emerging Alternative for Pain Control: Mechanism and Applications of Cryotherapy in Endodontics: Pharmaceutical Science-Dentistry and endodontics - Sarangi, Swayangprabha; Chandak, Manoj; Ikhar, Anuja; Dayanand, Mrinal; Jidewar, Namrata (International Journal of Life Science and Pharma Research, 2023)
Patient discomfort after conventional root canal therapy remains inevitable in endodontic practices. It depends onthe clinician to lessen the postoperative pain encountered by the patient. This review article aims to get acquainted withCryotherapy, a current modality designed to reduce patients’ anxiety, pain, and inflammation levels. Extensive studies have beenprovided on the applications of cryotherapy in the fraternity of medicine, but its utilization has been restricted in the Endodonticregime. Cryotherapeutic agents benefit in the regard that they eliminate the need for prescribing supplementary medications.The application of cryo-therapeutic agents is technique sensitive and requires the clinician to have thorough and correctknowledge regarding its underlying mechanism of action. Several expected outcomes can be derived after cryotherapyapplication. It is proven that intracanal application of the cryotherapeutic agent provides anodyne–like action serving as anessential tool for pain control. The concept of frozen tissues is related to ancient times, such as treating sports injuries, while itsrecent introduction into endodontics has been a boon to already practicing clinicians. Although it is a slow process requiringmultiple appointments of visits to the clinician, its long-term benefits can be a breakthrough in meeting the benefits of deliveringquality patient care. This article sheds light on its recent applications in endodontics, focusing on the chemistry behind freezingcells to newer advancements. However, significant and valid trials need to be carried out to reach evidence of certainty aboutthe therapeutic benefits and additional tools of delivery. It will pave the way for further scientific work to broaden its range ofapplications in dentistry.